A new species of Amolops (Anura: Ranidae) from southwestern Guangdong, China - Lyu, Zhi-Tong; Wu, Jun; Wang, Jian; Sung, Yik-Hei; Liu, Zu-Yao; Zeng, Zhao-Chi; Wang, Xin; Li, You-Yu; Wang, Ying-Yong (Zootaxa, 2018)
A new species, Amolops yunkaiensis sp. nov. is described based on a series of specimens from Ehuangzhang Nature Reserve and Yunkaishan Nature Reserve, southwestern Guangdong Province, China. The new species can be distinguished from all known congeners by molecular divergence in the mitochondrial 16S rRNA, 12S rRNA and CO1 genes, and a combination of the following characters: relatively small body size, SVL 31.8–34.1 mm in adult males, 35.2–39.0 mm in adult females; numerous raised large warts on dorsum and flanks; dorsal body olive-brown or light brown with dark brown blotches; absence of vomerine teeth; absence of tarsal glands; presence of a pair of subgular vocal sacs, nuptial spines on the first finger, and sparse translucent tubercles on the lower jaw, forechest, posterior belly and ventral thigh in male. Hence, the genus Amolops contains 52 species, 29 of which occur in China.